CYP3A4 and CYP3A5 genotyping by Pyrosequencing - McLeod Howard L; Garsa Adam A; Marsh Sharon (BMC, 2005)
Abstract Background Human cytochrome P450 3A enzymes, particularly CYP3A4 and CYP3A5, play an important role in drug metabolism. CYP3A expression exhibits substantial interindividual variation, much of which may result from genetic variation. This study describes Pyrosequencing assays for key SNPs in CYP3A4 (CYP3A4*1B, CYP3A4*2, and CYP3A4*3) and CYP3A5 (CYP3A5*3C and CYP3A5*6). Methods Genotyping of 95 healthy European and 95 healthy African volunteers was performed using Pyrosequencing. Linkage disequilibrium, haplotype inference, Hardy-Weinberg equilibrium, and tag SNPs were also determined for these samples. Results CYP3A4*1B allele frequencies were 4% in Europeans and 82% in Africans. The CYP3A4*2 allele was found in neither population sample. CYP3A4*3 had an allele frequency of 2% in Europeans and 0% in Africans. The frequency of CYP3A5*3C was 94% in Europeans and 12% in Africans. No CYP3A5*6 variants were found in the European samples, but this allele had a frequency of 16% in the African samples. Allele frequencies and haplotypes show interethnic variation, highlighting the need to analyze clinically relevant SNPs and haplotypes in a variety of ethnic groups. Conclusion Pyrosequencing is a versatile technique that could improve the efficiency of SNP analysis for pharmacogenomic research with the ultimate goal of pre-screening patients for individual therapy selection.